Copper-Induced Activation of Trps and Vdccs Triggers a Calcium Signature Response Regulating Gene Expression in Ectocarpus Siliculosus - Moenne-Munoz, A; Gonzalez-Figueroa, A (PeerJ Inc., 2018)
In certain multicellular photoautotrophs, such as plants and green macroalgae, it has been demonstrated that calcium signaling importantly mediates tolerance to copper excess. However, there is no information in brown macroalgae, which are phylogenetically distant from green algae and plants. We have previously shown that chronic copper levels (2.5 μM) activate transient receptor potential (TRP) channels in the model brown macroalga Ectocarpus siliculosus, allowing extracellular calcium entry at 13, 29, 39 and 51 min. Here, we showed that intracellular calcium increases also occurred at 3 and 5 h of exposure; these increases were inhibited by antagonists of voltage-dependent calcium channels (VDCCs); a chelating agent of extracellular calcium; an antagonist of endoplasmic reticulum (ER) ATPase; and antagonists of cADPR-, NAADP- and IP3-dependent calcium channels. Thus, copper activates VDCCs allowing extracellular calcium entry and intracellular calcium release from the ER via cADPR-, IP3- and NAADP-dependent channels. Furthermore, the level of transcripts encoding a phytochelatin synthase (PS) and a metallothionein (MT) were analyzed in the alga exposed to 2.5 μM copper from 3 to 24 h. The level of ps and mt transcripts increased until 24 h and these increases were inhibited by antagonists of calmodulins (CaMs), calcineurin B-like proteins (CBLs) and calcium-dependent protein kinases (CDPKs). Finally, activation of VDCC was inhibited by a mixture of TRP antagonists and by inhibitors of protein kinases. Thus, copper-mediated activation of TRPs triggers VDCCs via protein kinases, allowing extracellular calcium entry and intracellular calcium release from ER that, in turn, activate CaMs, CBLs and CDPKs increasing expression of PS and MT encoding genes in E. siliculosus. © 2018 González et al.